ESTIMATING MARINE RESERVOIR EFFECTS IN ARCHAEOLOGICAL CHRONOLOGIES: COMPARING ΔR CALCULATIONS IN PRINCE RUPERT HARBOUR, BRITISH COLUMBIA, CANADA. Issue 4 (October 2018) - Martindale, Andrew; Cook, Gordon T.; McKechnie, Iain; Edinborough, Kevan; Hutchinson, Ian; Eldridge, Morley; Supernant, Kisha; Ames, Kenneth M.
Abstract : The best method for quantifying the marine reservoir effect (MRE) using the global IntCal Marine13 calibration curve remains unresolved. Archaeologists frequently quantify uncertainty on MRE values as errors computed from single pairs of marine-terrestrial radiocarbon ages, which we argue significantly overstates their accuracy and precision. Here, we review the assumptions, methods, and applications of estimating MRE via an estimate of the additional regional offset between the marine and terrestrial calibration curves (ΔR) for the Prince Rupert Harbour (PRH) region of British Columbia, Canada. We acknowledge the influence on ΔR of MRE variation as (1) a dynamic oceanographic process, (2) its variable expression in biochemical and geochemical pathways, and (3) compounding errors in sample selection, measurement, and calculation. We examine a large set of marine-terrestrial pairs ( n = 63) from PRH to compare a common archaeological practice of estimating uncertainty from means that generate an uncertainty value of ±49 years with a revised, more appropriate estimate of error of ± 230 years. However, we argue that the use of multiple-pair samples estimates the PRH ΔR as 273 ± 38 years for the last 5, 000 years. Calculations of error that do not consider these issues may generate inaccurate age estimates with unjustifiable precision. Abstract : El mejor método para cuantificar el efecto reservorio marino (MRE, por sus siglas en inglés) usando la curva global de calibración IntCal Marine 13 permanece sin resolver. Los arqueólogos frecuentemente cuantifican la incertidumbre en valores del MRE como errores calculados a partir de pares únicos de edades radiocarbónicas marinas y terrestres que, sostenemos, sobrevaloran significativamente su exactitud y precisión. Aquí revisamos las suposiciones, métodos y aplicaciones para estimar el MRE a través de una estimación de la compensación regional adicional entre las curvas de calibración marinas y terrestres (ΔR) para la región de Prince Rupert Harbour (PRH) en Columbia Británica, Canadá. Reconocemos la influencia sobre el ΔR de variaciones del MRE como (1) un proceso oceanográfico dinámico, (2) su expresión variable en caminos bioquímicos y geoquímicos que producen muestras para datación 14 C por AMS y (3) errores compuestos en la selección de muestras, mediciones y cálculos. Examinamos un amplio conjunto de pares marinos-terrestres (n = 63) procedentes de PRH para comparar la práctica arqueológica común de estimar la incertidumbre a partir de promedios que generan un valor de incertidumbre de ±49 años, con una estimación de error revisada, más apropiada, de ±230 años. Este acercamiento estima el ΔR de PRH en 273 ± 38 años para los últimos 5, 000 años. Los cálculos de error que no consideran estas cuestiones pueden generar estimaciones inexactas de edad con precisiones injustificables.